European Competence Network on Mastocytosis (ECNM): 10-year jubilee, update, and future perspectives = European Competence Network on Mastocytosis (ECNM) : 10-Jahres Jubiläum, Erfolgsbilanz und Zukunftsperspektiven - Valent, Peter; Reiter, Andreas (Wiener klinische Wochenschrift, 2012)
Summary: The European Competence Network on Mastocytosis (ECNM) was initiated in 2002 as a multidisciplinary and multinational cooperative approach to increase awareness and to improve diagnosis and therapy of mastocytosis. The network is composed of local centers, physicians, and scientists who have dedicated their work to patients with mastocytosis. A strategic goal of the ECNM is to provide the best available information about the disease to patients and physicians. During the past 10 years, the ECNM has expanded to various countries and contributed successfully to the development of markers, definitions, and standards in the field of mastocytosis. Members of the ECNM organized Annual Meetings in Europe and two Working Conferences on Mastocytosis in Vienna (in 2005 and 2010), and initiated and supported several preclinical and clinical trials. In all these activities, representatives of the ECNM cooperate closely with their US colleagues, with patient-organizations in Europe and in the USA, and with other scientific networks. The ECNM also launched a mastocytosis registry that has been activated in 2012. Using the central database of this registry, cooperative multicenter studies, which should include sufficient numbers of patients and robust evaluations, will be conducted. These studies will increase our knowledge about optimal management and therapy of patients with mastocytosis in the future.
Gesehen am 24.10.2018